A survey on modularity and distributivity in series-parallel hybrid robots. (June 2020) - Kumar, Shivesh; Wöhrle, Hendrik; de Gea Fernández, José; Müller, Andreas; Kirchner, Frank
Abstract: Parallel mechanisms are used increasingly often as modular subsystem units in various robots and man-machine interfaces for their superior stiffness, payload-to-weight ratio and dynamic properties. This leads to series-parallel hybrid robotic systems which utilize closed loop linkages and parallel kinematic machines as an abstraction of a certain kinematic joint. This paper presents a survey of recently developed series-parallel hybrid robots in various application domains such as legged robotics, humanoids, exoskeletons and industrial automation. In particular, we focus on modular and distributive aspects of such systems with an intention to bring their current design paradigm into focus, which simplifies the robot development process by promoting the effective reuse of hardware and software components and overcomes the shortcomings of traditional serial robots like poor payload capacity and stiffness.